COMPARING THE CONVENTIONAL AND SHARIA MONEY MARKET: AN INDONESIAN CONTEXT - Ana Nur Anisah; Joko Hadi Purnomo (International Conference on Social and Islamic Studies, 2021)
This research aimed to determine the analysis of conventional financial market instrument and Islamic money markets in Indonesia. Money market is a mechanism for trading funds in the short term, i.e. funds with a maturity of less than one year. Whereas Islam views money only as a medium of exchange, not commodities or merchandise. The research method uses the library research method. Where researchers do not directly conduct research in a company, but use the library as a source of data needed. The results obtained can be concluded as follows: 1. The difference between conventional financial markets and Islamic financial markets lies in the mechanism of control. On conventional financial markets, instruments issued are instruments sold at a discount and based on interest calculations. While the Islamic money market is more complex and approaches the capital market mechanism, which contains investment, cooperation and others namely Mudharabah, Musyarakah, qard, and Wadi’ah but only in the short term; 2. Instruments on conventional money markets include bank Indonesia certificates, money market securities, certificates of deposit, Commercial Paper, Call Money, Repurchase Agreement, Banker's Acceptance; 3. Instruments on the Islamic money market include inter-bank investment certificates, Mudharabah money market securities and bank Indonesia wadi’ah certificates.